Beclin-1–Dependent Autophagy Improves Outcomes of Pneumonia-Induced Sepsis - Nikouee, Azadeh; Kim, Matthew; Ding, Xiangzhong; Sun, Yuxiao; Zang, Qun S. (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: We previously demonstrated that promoting Beclin-1-dependent autophagy is cardiac protective during endotoxemia shock, suggesting that autophagy-based approaches may become a promising therapeutic strategy for sepsis. In this study, we applied both genetic and pharmacological approaches to evaluate whether Beclin-1 activation improves sepsis outcomes in a model of pneumonia-induced sepsis. Methods: Sepsis was induced in mice by Klebsiella pneumoniae infection via intubation, and outcomes of clinical sickness scores, systemic infection, inflammation, survival, and pulmonary pathology were examined. Evaluation of Beclin-1 activation was achieved by comparing strains of C57BL/6J wild type and Becn1F121A that carries a transgenic expression of Beclin-1 active mutant F121A, and by comparing animal groups treated with Beclin-1 activating peptide, Tat-beclin-1 peptide (TB-peptide), or with vehicle control. The status of autophagy in the lung tissue was examined in autophagy reporter mice, CAG-RFP-EGFP-LC3, by fluorescence microscopy. Results: Pulmonary infection by K. pneumoniae produced an insufficient, maladaptive autophagy in the lung. Activation of Beclin-1 by forced expression of active mutant Becn1F121A or by treatment with TB-peptide enhanced autophagy and significantly reduced sickness scores, systemic infection, and circulating and pulmonary cytokine production. Both approaches demonstrated notable benefits in limiting post-infection pathogenesis in the lung, such as decreases in alveolar congestion, hemorrhage, infiltration of inflammatory cells, and alveolar wall thickness. Conclusion: Data suggest that targeted activation of Beclin-1 alleviates adverse outcomes of pneumonia-induced sepsis, and thus, possess a therapeutic potential.